THE MAIN CHARACTER'S INDEPENDENCE IN QAISRA SHAHRAZ'S THE HOLY WOMAN - Gentry Regina; Agnes Setyowati H; Shita Dewi Ratih P (Journal Albion : Journal of English Literature, Language, and Culture, 2020)
The purpose of this thesis is to point out the main character’s independence in Qaisra Shahraz’s The Holy Woman, and to identify measures that she has undertaken to fight for her independence in confronting the tradition in Pakistan. Using descriptive qualitative methods and feminist studies, it is  learned that the main character is a common but strong woman who must serve as a “Holy Woman” and “marry” the Quran. Because of the old tradition and  culture that still exist in Pakistan, the main character gradually develops her traits and becomes a dynamic character accordingly. Keywords: culture, feminism, Pakistan, patriarchy, tradition